PENERTIBAN GELANDANGAN DAN PENGEMIS GUNA MENINGKATKAN PARIWISATA DI KOTA DENPASAR - Rahmitha Parta Dewi, Kadek; Dirksen, A. A. Ngurah Gede (Kertha Negara : Journal Ilmu Hukum; Vol. 01, No. 03, Mei 2013)
This paper titled "Control of Vagrants and Beggars to increase tourism in Denpasar City". Tourism in Denpasar is one sector that is very influential on regional income, the problems of tourism must be considered both in terms of facilities, human resources, cultural traditions should always be preserved as well as security and order, which is currently very complicated to be overcome particular problems vagrants and beggars, due to flow of urbanization so that the public looking for jobs to the city. How to bring order and overcome vagrants and beggars to improve tourism and how to sanctions for vagrants and beggars who violate order. This type of research is used an empirical legal research, the studies in terms of the written rules. The results obtained are the control and countermeasures of vagrants and beggars stipulated in Government Regulation No. 31 of 1980, there is an element in the regulation of preventive, repressive, and rehabilitative and Denpasar City Regional Regulation No. 15 of 1993 Article 35 paragraph (4) stated prohibited activities may or begging or begging or busking or other business like, if it is violated will be subject to the maximum fine of Rp. 50.000, - (Fifty Thousand Rupiah).
Keywords: Denpasar City, Tourism, Management and control, Vagrants and Beggars